Witches - Kallen, Stuart A. 1955- (San Diego, Calif.: Lucent Books, 2000)
Discusses witches, including ancient witches; the years between 1450 and 1700 during which time people accused of being witches were violently persecuted; witchcraft today; and magic and spells.
Includes bibliographical references and index.
Keywords: Witchcraft -- Juvenile literature. -- History; Witchcraft -- History